A unique association of arrhythmogenic right ventricular dysplasia and acute myocarditis, as assessed by cardiac MRI: a case report. Issue 1 (December 2016) - Ponsiglione, Andrea; Puglia, Marta; Morisco, Carmine; Barbuto, Luigi; Rapacciuolo, Antonio; Santoro, Mario; Spinelli, Letizia; Trimarco, Bruno; Cuocolo, Alberto; Imbriaco, Massimo
Abstract Background Arrhythmogenic right ventricular dysplasia (ARVD), is a genetic disorder of the heart, which mainly involves the right ventricle. It is characterized by hypokinetic areas at the free wall of the right ventricle (RV) or both ventricles, where myocardium is replaced by fibrous or fatty tissue. ARVD is an important cause of ventricular arrhythmias in children and young adults. Although the transmission of the disease is based on hereditary, in young adults it may not show any symptoms. The main differential diagnoses with other frequent etiological causes of sudden arrhythmia are: idiopathic outflow tract ventricular tachycardia of the RV, myocarditis, dilated cardiomyopathy and sarcoidosis. Case presentation We describe an unusual case of a 44-year-old woman who was hospitalized for ventricular tachycardia, deep asthenia and dyspnoea with no previous history of cardiac disease. The patient had a ten-year history of palpitations, which started immediately after her last pregnancy. She was diagnosed with both acute/subacute viral myocarditis and arrhythmogenic right ventricular dysplasia, based on established clinical and cardiac MRI criteria. After the diagnosis the patient received an automatic implantable cardioverter defibrillator. Currently, she is on clinical follow-up with no apparent further complications. Conclusion Analyzing this rare case, we have shown the link between myocarditis and arrhythmogenic right ventricular dysplasia, and how important is to perform a cardiac MRI, in the context of acute myocarditis and ventricular arrhythmia.